Bacteria Isolation from Public Cemeteries Soil and Test for Resistance to Antibiotics - Laspartriana, Anggita Juniar; Rahayu, Triastuti; Tyastuti , Erma Musbita; Sidiq , Yasir (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: A public burial place (TPU) is used to bury the dead. There is an active decomposition of corpses in the soil, which produces soil nutrients and minerals that can support the growth of microorganisms in the ground, including pathogenic bacteria. Pathogenic bacteria have a more severe impact if they are resistant to antibiotics. Methods: Soil samples were taken in the Bonoloyo TPU area, Surakarta, Central Java, at 3 points each of 2 depths of 20 and 50 cm. Soil samples were inoculated on NA (Nutrient agar) media using the spread plate method. After 48 hours, colony counting and morphology observations were carried out, followed by gram staining. Isolated bacterial isolates were tested for resistance to 3 types of antibiotics. Results: The average population of soil bacteria in blocks 12, 17, and 21 at a depth of 20 cm is 4 x 10⁶ CFU/g; 8 x 10⁶ CFU/g; and 1 x 10⁶ CFU/g, while at a depth of 50 cm, it is 2.3 x 10⁶ CFU/g; 6 x 10⁶ CFU/g; and 4 x 10⁶ CFU/g. The morphology of bacterial colonies is irregular (26 isolates), flat elevation (19 isolates), and the color of isolates is predominantly white. The Gram staining results obtained 23 isolates are Gram-negative, and 22 are Gram-positive with a dominant cell form in cocci. Antibiotic resistance tests showed that the bacterial isolates were resistant to ampicillin (28.9%), Bacitracin (64.4%), and Cefepime (57.8%). Conclusions: Burial soil bacterial populations at Bonoloyo TPU at different depths did not differ markedly, with numbers ranging from 1 - 8 x 10⁶ CFU/g.